Distribution and sources of heavy metals in stream sediments in Tum Talu watershed Bunnung Sata Yala Southern Thailand - Nannapat Natchakunlasap (Chulalongkorn University, 2007)
Thesis (M.Sc.) -- Chulalongkorn University, 2004